ANALYSIS OF PALM OIL FARMING INCOME IN KOGEM VILLAGE, MARBAU DISTRICT, NORTH LABUHANBATU REGENCY - Dimas Kurniawan; Khairul Rizal; Badrul Ainy Dalimunthe; Yusmaidar Sepriani (RADJA PUBLIKA, 2026)
This study aims to analyze the income of oil palm farming businesses in Kogem Village, Marbau District, Labuhanbatu Regency, consisting of production costs, revenue, income, and the revenue-to-cost ratio in oil palm farming. The sampling method used in this study was purposive sampling. This study collected data using primary and secondary data. Data analysis was conducted to calculate costs, revenue, income, and the R/C ratio. The results showed that the R/C ratio for oil palm farming was 3.48, meaning that every Rp. 100.00 additional costs incurred by the entrepreneur will generate Rp. 3.48.00 in revenue. This value is greater than 1, making palm oil farming economically profitable.